Digitalisasi Marketing untuk Pemberdayaan UMKM sebagai Wujud Kemandirian Ekonomi Pesantren (Studi pada Darku Asyikin-Ponpes Darussa’adah Kyai Haji Asyikin) - MS, Mahrinasari; Nikmah, Rokhimatun; Handayani, Fitri Melan; Purwa, I Putu; Harmein, Harmein; Siregar, Maria; Siregar, Rony (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2024)
ABSTRACT"Pondok pesantren," or Islamic boarding schools, are known as places of education that focus on religious studies. With the passage of time, these schools have developed an awareness of economic self-sufficiency. For example, Darussa'adah Kyai Haji Asyikin's Islamic boarding school follows the Salafist system, which involves studying traditional Islamic texts as a fundamental part of its curriculum. Today, this institution has ventured into economic independence by establishing business units. To further develop these businesses, it is crucial to increase awareness and provide knowledge about marketing strategies, especially through the use of digital technology. Efforts to enhance awareness and promote the growth of these businesses should include providing knowledge and understanding of digital marketing strategies. Small and Medium Enterprises (UMKM) require appropriate strategies for the implementation of digital marketing, such as creating attractive promotional designs that highlight the uniqueness and advantages of their products. The research methodology applied in this study involves sharing knowledge through discussions and presentations on optimizing social media accounts and various e-commerce platforms. Additionally, integrating the business address on Google Maps is essential. The presentation on digital marketing aims to stimulate creativity and innovation, ultimately assisting in the advancement of UMKM, particularly those associated with Islamic boarding schools.Keywords: Digitalization, MSMEs, Islamic Boarding School Economic Independence    ABSTRAKPondok pesantren dikenal sebagai tempat pendidikan yang mengkaji mengenai ilmu agama. Seiring berkembangnya zaman, Pondok pesantren telah memiliki kesadaran dalam hal kemandirian ekonomi. Seperti halnya Pondok pesantren Darussa’adah Kyai Haji Asyikin merupakan pondok dengan sistem salafiyah dengan mengkaji kitab kuning sebagai acuan belajarnya, saat ini telah memiliki unit usaha sebagai bentuk kemandirian ekonominya. Upaya yang dapat dilakukan untuk meningkatkan kesadaran untuk menjadikan usahanya berkembang yaitu perlu adanya pemberian pengetahuan serta pemahaman mengenai strategi pemasaran dengan pemanfaatan teknologi digital. UMKM memerlukan strategi yang tepat dalam pengaplikasiannya terhadap digitalisasi marketing seperti halnya desain promosi yang menarik dan menampilkan keunikan dan keunggulan produk.. Metode yang diterapkan dalam penelitian ini dngan memberikan pengetahuan melalui diskusi dan pemaparan materi mengenai optimalisasi pada akun media sosial dan berbagai e-commerce serta memasukkan Alamat umkm pada google maps. Pemaparan mengenai digitalisasi marketing diharapkan mampu mengambangkan kreativitas dan inovasi sehingga dapat membantu memajukan umkm terutama pada pondok pesantren.Kata Kunci: Digitalisasi, UMKM, Kemandirian Ekonomi Pesantren